(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Olesya B. Soldatova (Barnaul, Russian Federation) The article is devoted to the study of the axiological potential of familiar-colloquial lexeme kid, determined by the word stylistic marking and the content of the conceptual-cognitive frame “child”, in the text of the British press. The divergence of the lexeme usage pragmatics and the context pragmatics is the source of the creation of a high-intensity axiological evaluation in the text. For the purpose of analyzing the contextual actualization of evaluation meanings, five clusters are identified in the structure of this conceptual-cognitive frame, the influence of their sub-frames plays a decisive role in the evaluation creation in the British media text. As an empirical material, there are cases of creating a negative evaluation at actualization of the lexeme meliorative-estimated connotations. The use of familiar-conversational word kid in media texts describing major social and political problems is a vivid example of the manipulation with public opinion and evaluation by the British media, since the child is the most vulnerable member of the society, causing empathy from the overwhelming majority of the audience. The study of the use of the usually-implicitly evaluative conversational vocabulary in cases of determination of the assessment at the context level due to the influence of the subframes of clusters of the corresponding conceptual-cognitive frame and the familiar-colloquial marking of the lexeme gives a more detailed idea of the axiological potential of the adherently-evaluative vocabulary. Key words: axiological potential, colloquial marking, conceptualcognitive frame, subframe, cluster, contextual evaluation, usually-implicit evaluative vocabulary, familiar-colloquial lexeme. DOI 10.23683/1995-0640-2019-2-12-20